2021
DOI: 10.3390/jcm10050959
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Fecal Microbial Transplantations and Antibiotic Pre-Treatment Are Linked to Improved Clinical Response and Remission in Inflammatory Bowel Disease: A Systematic Review and Pooled Proportion Meta-Analysis

Abstract: The response of patients with inflammatory bowel disease (IBD) to fecal microbial transplantation (FMT) has been inconsistent possibly due to variable engraftment of donor microbiota. This failure to engraft has resulted in the use of several different strategies to attempt optimization of the recipient microbiota following FMT. The purpose of our study was to evaluate the effects of two distinct microbial strategies—antibiotic pre-treatment and repeated FMT dosing—on IBD outcomes. A systematic literature revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
29
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 76 publications
3
29
0
5
Order By: Relevance
“…According to meta-analyses, half of the UC patients receiving FMT display a response to treatment, and one third achieve clinical remission of their symptoms. (3)(4)(5)(6) after FMT. Across four randomized, placebo-controlled studies (RCTs) (7-10), 28% of FMT and only 9% of placebo recipients achieved remission (4).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to meta-analyses, half of the UC patients receiving FMT display a response to treatment, and one third achieve clinical remission of their symptoms. (3)(4)(5)(6) after FMT. Across four randomized, placebo-controlled studies (RCTs) (7-10), 28% of FMT and only 9% of placebo recipients achieved remission (4).…”
Section: Introductionmentioning
confidence: 99%
“…Most include an initial dose via colonoscopy, and many follow up with a maintenance dose regimen ranging from just once three weeks after the initial dose (7) to five times a week for two months (9). Maintenance doses may improve efficacy (6), but their cost and tolerability are substantial challenges. The recent development of FMT capsule formulations may make maintenance dosing logistically easier and more acceptable to patients (15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%
“…We found that the relative abundances of Prevotella, Blautia, Coprococcus, Anaerostipes, and Ruminococcus were lower in the gut microbiota of PA patients than in healthy controls and primary hypertension patients. All these bacteria could produce SCFAs (18)(19)(20)(21). SCFAs, the energy sources of enterocytes, could maintain the intestinal epithelial barrier and decrease the permeability of the gut, circulating lipopolysaccharides, and systemic inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…A prior study also found that the relative abundance of Dialister in children with autism spectrum disorder was decreased ( Andreo-Martínez et al, 2020 ). Additionally, Prevotella, which is a short-chain fatty acid producing anaerobes ( Mocanu et al, 2021 ), was found to be implicated in the development of severe gastrointestinal symptoms ( Tan et al, 2021 ). These bacteria with the same changing trend in different intestine sites may guide future research on understanding the pathophysiology behind SIBO or provide insight into potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%